Pengaruh Penempatan Kerja dan Beban Kerja terhadap Kinerja Pegawai dengan Kepuasan Kinerja Sebagai Variabel Intervening - Hasrival, Hasrival; Sari, Vivi Nila; Pratiwi, Nila (Politeknik Baubau, 2024)
Employee performance is one of the indicators that is measured to see the extent to which an employee is able to work according to predetermined standards. Several factors that influence employee performance include work placement and workload. Work placement is a qualification for the position or place where the employee works. Workload also influences performance, the more workload an employee has, the more problems they face. This research aims to examine the effect of work placement and workload on employee performance with job satisfaction as an intervening variable. Primary data was obtained by distributing questionnaires to 34 employees as respondents at the Pasaman Regency Regent's Office. The analysis tool is Structural Equation Modeling (SEM) using Partial Least Square (PLS). The results of the research show that work placement and workload have a positive and significant influence on job satisfaction at the Pasaman Regency Regent's Office. Work placement has a positive and significant influence on employee performance, workload and job satisfaction has a positive and insignificant influence on employee performance. Job satisfaction has a positive and insignificant influence on employee performance at the Pasaman Regency.